Apakah Sektor Agrikultur masih Merupakan Ujung Tombak Kesejahteraan Masyarakat di Provinsi Lampung? - Firda Maharani Anwar (Syntax Literate, 2023)
This research aims to determine whether the Agriculture, Forestry, and Fisheries sectors are relied upon in the economy of regencies/cities in Lampung province, both in the present and future, to identify the growth rate and competitiveness of these related sectors, as well as to identify strategies that can be undertaken by the Lampung regional government to develop these sectors. The research method used is descriptive quantitative analysis, utilizing Location Quotient (LQ), Dynamic Location Quotient (DLQ), and shift share analysis. The results of the research indicate that the Agriculture, Forestry, and Fisheries sectors are the basis for 12 regencies/cities and have potential in 3 regencies/cities. Based on the shift share analysis, it is found that 6 regencies/cities fall into quadrant III and 9 others fall into quadrant IV. Based on the findings of this research, the government needs to formulate comprehensive policies in the agricultural sector to further develop the agriculture sector as a comparative advantage in Lampung province.